Peran Komunikasi Politik Pemerintah Dalam Mencegah Disintegrasi Bangsa - Supriyatno, Yanto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
One of the functions of political communication is to give information from top to bottom or vice versa, and with this horizontal information system will produse a mutual understanding between the state / government and organizations that become their subordinate. Political communication is a tool in managing, coordinating and regulate state institutions vertically or horizontally.